Small Businesses and Entrepreneurship in Times of Crises: The Renaissance of Entrepreneur-Focused Micro Perspectives. (March 2022) - Newman, Alexander; Obschonka, Martin; Block, Joern
Prior research examining the consequences of crises for small businesses and entrepreneurial ventures has typically applied a macro-perspective, focussing on the impact of crises on business organisations and the strategies they adopt in times of crisis. In this editorial, we review the articles that form part of our special issue on 'Small Businesses and Entrepreneurship in Times of Crises', after introducing an entrepreneur-focused multi-level conceptual model. Highlighting the importance of integrating both micro- and macro-perspectives, the model facilitates our understanding as to how entrepreneurs and the organisations they run respond to unexpected crises such as the COVID-19 pandemic. We conclude with implications for future research.